How do you build a nectar spur? A transcriptomic comparison of nectar spur development in Linaria vulgaris and gibba development in Antirrhinum majus - Cullen, Erin; Wang, Qi; Glover, Beverley J. (Frontiers in Plant Science, 2023)
Nectar spurs (tubular outgrowths of floral organs) have long fascinated biologists. However, given that no model species possess nectar spurs, there is still much to learn about their development. In this study we combined morphological analysis with comparative transcriptomics to gain a global insight into the morphological and molecular basis of spur outgrowth in Linaria. Whole transcriptome sequencing was performed on two related species at three key developmental stages (identified by our morphological analysis), one with a spur (Linaria vulgaris), and one without a spur (Antirrhinum majus). A list of spur-specific genes was selected, on which we performed a gene enrichment analysis. Results from our RNA-seq analysis agreed with our morphological observations. We describe gene activity during spur development and provide a catalogue of spur-specific genes. Our list of spur-specific genes was enriched for genes connected to the plant hormones cytokinin, auxin and gibberellin. We present a global view of the genes involved in spur development in L. vulgaris, and define a suite of genes which are specific to spur development. This work provides candidate genes for spur outgrowth and development in L. vulgaris which can be investigated in future studies.